Preferreds - winans Kenneth G. (KGW Publishing, 2007)
Mr. Market by William Gibson An exchange traded fund (ETF) for preferred stocks, U.S. Preferred Stock iShares (PFF), is now trading. Speaking of preferred stocks, a new book (Preferreds, Wall Street s Best Kept Income Secret was recently written and published by Novato, California-based money manager, Ken Winans. It s a good primer, probably the best book ever written on the subject, including technical considerations. Ken s research shows a 40-week moving average works best. --Mr. Market 4/2007